THE Pengaruh Permainan Taman Lempar Terhadap Motivasi Belajar Anak - Kurniawan, Muhammad Damarjati; Supriyadi, Tedi; Rukmana, Anin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the learning of the throwing park game motivation to learn physical education. Researchers took a sample of 22 elementary school students in grades V and VI. This research uses a quantitative type with an experimental method with a One-Group pretest posttest design. This research data collection used motivational questionnaires for students and statistical applications to obtain final results. At the beginning of the student learning motivation test, many students still lacked motivation; when given treatment, the students played the game well and smoothly. The results of this research were that there was an increase of 33.5% in children's learning motivation. In conclusion, the Taman Throwing game influences children's learning motivation. Keywords: Physical Education, Motivation, Throwing